Factors associated with infant formula supplementation in Brazilian hospitals: a cross-sectional study - Laís Araújo Tavares Silva; Maria Inês Couto de Oliveira; Ana Carolina Carioca da Costa; Samira Fernandes Morais dos Santos; Silvana Granado Nogueira da Gama; Vânia de Matos Fonseca (Elsevier, 2022)
Objective: To analyze the factors associated with infant formula supplementation in newborns referred to rooming-in in Brazilian hospitals. Method: Cross-sectional study with data from 14,531 postpartum women and newborns obtained from the ''Birth in Brazil'' survey, conducted in 2011-2012. The analysis used a logistic regression model with a hierarchical approach. Results: In total, 21.2% newborns received infant formula during hospital stay. After adjustment, the following factors were associated with the use of infant formula: maternal age ≥ 35 years (OR = 1.51; IC95%:1.30-1.75), prenatal care in a private service (OR = 2,22; IC:1.72-2.85)/public and private service (OR = 1.67; IC:1.24-2.23), cesarean delivery (OR = 1.83; IC:1.41-2.38), multiple pregnancy (OR = 3.786; IC:2.02-7.06), non-breastfeeding in the delivery room (OR = 1.780; IC:1.43-2.21), birth in a private hospital (OR = 1.695; IC:1.02-2.79), prematurity (OR = 1.656; IC:1.32-2.06) and extremes of birth weight (< 2.500 g: OR = 2.084; IC: 1.585-2.741/ ≥4,000g: OR = 1.672; IC:1.31-2.11). Teenage age (OR = 0.651; IC:0.55-0.76), low maternal education (OR = 0.579; IC:0.43-0.77), multiparity (OR = 0.588; IC:0.510-0.678), and lower economic class (OR = 0.565; IC:0.41-0.76) significantly reduced the probability of using infant formula. Conclusions: Of the associated factors, the authors highlight cesarean delivery and non-breastfeeding in the delivery room, showing that it is necessary to strengthen policies that encourage good practices during childbirth care in order to promote exclusive breastfeeding and protect mothers and newborns from all social classes against the misuse of infant formula.